NOTE: EFFECT OF SETT TYPE ON THE PERFORMANCE OF TUGUI [Dioscorea esculenta (Lour) Burk.] - Dingal , Alfredo G.; Pido, Nestor L.; Ecleo, Daniel G. (Annals of Tropical Research, 1987)
Sett types of tugui [Dioscorea esculenta (Lour) Burk.] could be arranged in order of increasing mortality and decreasing yield as follows: wholes, heads, tails and middles. Whole setts and middle setts had the highest and the lowest percentage emergence, respectively. The inability of some setts to germinate was attributed to tuber rot that resulted in death of setts. The number of sprouts did not differ among sett types but yield significantly differed mainly due to differences in mortality among sett types.